People’s Trust in a Virtual Project Team: Results of a Game Experiment - Setyanitami, Vera; Arini, Hilya Mudrika; Lathifah, Nurul (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study aims to: (1) find out the variables that influence people’s trust in the virtual team in a project, (2) find out the relationship of these variables with people trust in the virtual team in a project, and (3) the relationship between the presence of experienced members on a virtual team in leading an organization to determine the success of a project. The experiment was conducted using online Werewolf game and collected questionnaires from 30 respondents that divided into 3 groups, i.e., (1) having experience of being leaders, (2) a combination of having and having no experience of being leaders, and (3) having no experience of being leaders. A correlation test and a comparative test were used to analyze the result. The results found four variables that could influence people’s trust, i.e., (1) ability, (2) benevolence, (3) integrity, and (4) task faithfulness. All variables had a positive effect, except for task faithfulness. There is a relationship between the presence of leaders in a virtual team to the success of the project.